Simulador do reator UASB para conversão de vinhaça em biogás - SOUSA, Eduardo Augusto Fabiano de (2014)
In the production of ethanol from sugar cane as raw material, the vinasse is a sub product which is rich in mineral composites with high level of organic material substances. One of the alternatives used for the utilizing the sub products is the biogas (methane) production by upflow anaerobic sludge blanket (UASB). In accordance with some researches, the biogas produced has an energetical potential competitive with others energy sources. A simulator capable to produce results of this biogas production could represents an available tool for investments in the energy sector as well as to give informations to improve ethanol productive processes. The mass balance equations representing the UASB can be solved for establishing the gas volume produced from a certain vinasse mass, as well as to permit a detailed analyze of the physical and chemical vinasse properties. These properties consist of the available flow of the effluent of vinasse, the value of BOD (Biochemical Oxygen Demand) and COD (Chemical Oxygen Demand) and the temperature of the effluent. It is holped to make an easily simulated having an interface for the user and which permits the including of parameters for the productive process of ethanol.